Behavioural portfolio theory revisited: lessons learned from the field. (22nd May 2020) - Oehler, Andreas; Horn, Matthias
Abstract: We examine the relation between households' wealth and relative risk aversion (RRA) in two different frameworks: the Behavioural Portfolio Theory (BPT) and Merton's consumption and portfolio choice model (CPCM). We apply the BPT to field data for the first time and show that the BPT provides a better fit than the CPCM to explain the financial risk‐taking of the households in Deutsche Bundesbank's Panel on Household Finances survey. However, both models indicate decreasing RRA. While households' education and financial literacy hardly improve the fit of either model, households show different risk‐taking behaviour in accordance with their self‐assessed risk attitude.